Legion of Memory: Performance at Branch 51 - Bennett, Melanie (Theatre Research in Canada / Recherches théâtrales au Canada, 2008)
Legion of Memory is a site-specific performance co-created by Melanie Bennett and Andrew Houston, which was staged in an abandoned legion hall in downtown Kitchener, Ontario. Launched in June 2006 and remounted in April 2007, Legion of Memory attempts to animate the cultural displacement of the war veteran and refugee, while also exploring issues surrounding war memorials in Canada today. Résumé Legion of Memory est un spectacle créé par Melanie Bennett et Andrew Houston dans une filiale abandonnée de la Légion, au centre-ville de Kitchener, en Ontario. Présenté pour la première fois en juin 2006 et repris en avril 2007, ce spectacle localisé cherche à illustrer le déplacement que vivent sur le plan culturel les anciens combattants et les réfugiés de guerre tout en explorant les enjeux actuels autour des monuments de guerre au Canada.